Peak broadening anisotropy in deformed face‐centred cubic and hexagonal close‐packed alloys. (1st October 2014) - Simm, T. H.; Withers, P. J.; Quinta da Fonseca, J.
<x xml:space="preserve">Abstract</x> The broadening of diffraction peaks representing different families of grain orientations has been measured for a number of deformed metals: austenitic stainless steel 316, nickel 200 and the titanium alloy Ti‐6Al‐4V. These measurements have been compared with predictions that explain differences in broadening in terms of the contrast factor of dislocations via two different approaches. This was done in order to understand the effect the contrast factor has on the results of diffraction peak profile analysis methods and the cause of broadening anisotropy. An approach that considers all grains and orientations to behave similarly was found to be unsuccessful in explaining the large variations of broadening in different peaks. These variations can be explained, and errors reduced, by adopting an approach that uses a polycrystal plasticity model. However, if the plasticity based approach is used to solely calculate changes in the contrast factor, it only partly explains changes in broadening. Instead, factors such as variations in the dislocation density and crystallite size in different orientations, the number of dislocations that are mobile, and the number of edge and screw dislocations need consideration. The way to incorporate these additional factors is difficult, but their contribution to broadening anisotropy can be as important as that of the contrast factor.